2015
DOI: 10.1590/1414-431x20144238
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin improves palmitate-induced insulin resistance in C2C12 myotubes by attenuating IRS-1/PI3K/Akt pathway inhibition

Abstract: The present study investigated the effect of silibinin, the principal potential anti-inflammatory flavonoid contained in silymarin, a mixture of flavonolignans extracted from Silybum marianum seeds, on palmitate-induced insulin resistance in C2C12 myotubes and its potential molecular mechanisms. Silibinin prevented the decrease of insulin-stimulated 2-NBDG (2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy-D-glucose) uptake and the downregulation of glutamate transporter type 4 (GLUT4) translocation in C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 33 publications
1
37
0
2
Order By: Relevance
“…This effect can be decreased by many natural substances like silibinin (principal flavonoid contained in silymarin, a mixture of flavonolignans extracted from Silybum marianum seeds). Silibinin prevents PI3K/AKT pathway inhibition by decreasing IRS1 phosphorylation on Tyr [24]. Similar mechanism is typical of PTP1B (protein-tyrosine phosphatase 1B), whose overexpression can inactivate the whole PI3K pathway [25].…”
Section: Irs Protein Nodementioning
confidence: 71%
“…This effect can be decreased by many natural substances like silibinin (principal flavonoid contained in silymarin, a mixture of flavonolignans extracted from Silybum marianum seeds). Silibinin prevents PI3K/AKT pathway inhibition by decreasing IRS1 phosphorylation on Tyr [24]. Similar mechanism is typical of PTP1B (protein-tyrosine phosphatase 1B), whose overexpression can inactivate the whole PI3K pathway [25].…”
Section: Irs Protein Nodementioning
confidence: 71%
“…It is widely known that insulin stimulates the Akt canonical pathway under physiological conditions [Li et al, ]. Phosphorylation of Akt at Ser 473 indicates the increment in insulin signaling by the ADSCs‐CM when compared to the diseases conditioned in C2C12 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results ( Figure 5 ) demonstrated that CmNo1 treatment leads to both the increased phosphorylation and enhanced expression of insulin receptor substrate 1 (IRS-1), protein kinase B (AKT), and glucose transporter type 4 (GLUT-4), indicating that the activated mediators subsequently increased insulin sensitivity. Many previous studies have already demonstrated the activation of IRS-1 and AKT via phosphorylation and GLUT-4 translocation as indicators of insulin sensitivity [ 55 60 ]. Additionally, high expression of GLUT-4 has also been reported to promote insulin-mediated glucose uptake [ 32 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%